2020
DOI: 10.3847/1538-4357/abc001
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Rotation of Young Massive Star Clusters in a Simulated Dwarf Starburst

Abstract: We analyze the three-dimensional shapes and kinematics of the young star cluster population forming in a high-resolution griffin project simulation of a metal-poor dwarf galaxy starburst. The star clusters, which follow a power-law mass distribution, form from the cold ISM phase with an IMF sampled with individual stars down to 4 solar masses at sub-parsec spatial resolution. Massive stars and their important feedback mechanisms are modelled in detail. The simulated clusters follow a surprisingly tight relatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 87 publications
(108 reference statements)
1
15
0
Order By: Relevance
“…(ii) Follow stellar dynamics: SF simulations that do not integrate stellar orbits explicitly generally discretize the stellar mass formed into a collisionless fluid represented by gravitationally softened particles (e.g. Grudić et al 2018a;Lahén et al 2019;Li et al 2019), which can produce qualitatively correct star cluster density profiles (Grudić et al 2018b;Lahén et al 2020), but have the severe limitation that the collisionless description (and phase-space density conservation) breaks down on mass scales M ࣠ 100 M , so if cluster formation is a hierarchical assembly from smaller masses (e.g. Bonnell, Bate & Vine 2003), then individual stellar dynamics is always important at some stage in the process.…”
Section: Requirements For a Complete Dynamical Model Of Star Formation And Feedbackmentioning
confidence: 99%
“…(ii) Follow stellar dynamics: SF simulations that do not integrate stellar orbits explicitly generally discretize the stellar mass formed into a collisionless fluid represented by gravitationally softened particles (e.g. Grudić et al 2018a;Lahén et al 2019;Li et al 2019), which can produce qualitatively correct star cluster density profiles (Grudić et al 2018b;Lahén et al 2020), but have the severe limitation that the collisionless description (and phase-space density conservation) breaks down on mass scales M ࣠ 100 M , so if cluster formation is a hierarchical assembly from smaller masses (e.g. Bonnell, Bate & Vine 2003), then individual stellar dynamics is always important at some stage in the process.…”
Section: Requirements For a Complete Dynamical Model Of Star Formation And Feedbackmentioning
confidence: 99%
“…Orbital motions may be isotropic even during the formation of GCs, for example Lahén et al (2020) have argued that the massive clusters are isotropic already during their first 100 Myr after formation. Moreover, as Lane et al (2010) and has shown, the interaction between the cluster and the galactic tidal field combined within the internal dynamics could produce complex kinematical features, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Here we aim to process the simulation output to match the data typically used in observational studies of young star clusters, and analyse the results using observationally verified methods. In Section 2 we first briefly introduce the simulation setup that has been extensively discussed in Lahén et al (2019), Lahén et al (2020a) and Lahén et al (2020b). In Section 3 we describe the post-processing and data reduction methods, including the radiative transfer modelling, synthetic photometry and star cluster detection.…”
Section: Introductionmentioning
confidence: 99%